Answer:
x = -9
y = -14
Step-by-step explanation:
We were given the following information:
![\begin{gathered} y=2x+4--------1 \\ y=x-5--------2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kxp5ksai82z0t2oe718vn90oty4ycsye2j.png)
We will calculate for the unknown variables using the Substitution Method as shown below:
![\begin{gathered} y=2x+4------1 \\ y=x-5------2 \\ \text{Since the subject of both equations is ''y'', we will proceed to equate both equations. We have:} \\ 2x+4=x-5 \\ \text{Put like terms together. We have:} \\ \text{Subtract ''x'' from both sides, we have:} \\ 2x-x+4=x-x-5 \\ x+4=-5 \\ \text{Subtract ''4'' from both sides, we have:} \\ x+4-4=-5-4 \\ x=-9 \\ \text{Substitute the value of ''x'' into equation 1 or 2 to obtain the value of ''y''. We have:} \\ y=x-5 \\ y=-9-5 \\ y=-14 \\ \\ \therefore x=-9,y=-14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6g8oj75k0tsqk0t045nh6zecw8r1wau29d.png)
Therefore, x equals -9 & y equals -14
The graphical solution is attached below: